Comparison of Collagen Granule Dressing Versus Conventional Dressing in Patients With Diabetic Foot Ulcer. (September 2022) - Colak, Bayram; Yormaz, Serdar; Ece, Ilhan; Çalişir, Akin; Körez, Kazım; Çınar, Mahmut; Sahin, Mustafa
Background . Diabetic foot ulcer (DFU) is a difficult, chronic wound with a significant long-term influence on the morbidity, mortality, and quality of life of patients. There is much information about the biochemical features of collagen and its function in wound healing. The aim of this study was to compare the results of DFU patients treated with and without collagen. Methods . A retrospective evaluation was made of the data of patients with DFU who underwent collagen treatment and physiological serum (PS) treatment. The patients were followed-up for a minimum of 12 weeks, and all complications, healing process, and wound characteristics were recorded. Results . Of the total 64 DFU patients included in the study, 30 were treated with PS and 34 with collagen. Complete closure was achieved in 17 (56.6%) of the PS group patients after 12 weeks of treatment. The rate was 25 (73.5%) in the collagen group. The mean duration of treatment was 9.2 weeks (range = 6-12 weeks) in the PS group and 8.08 weeks (range = 5-12 weeks) in the collagen group. The recovery time and recovery rates were determined to be better in the collagen group than in the PS group. Conclusion . A significant reduction in wound size was seen in the collagen group compared with the PS group. The results of this study demonstrated that collagen dressings are better than conventional dressings with regard to early granulation tissue and shorter hospital stay.